Do NPM Strategies Lead to Negative Organizational Behavior? Lessons from the Differential Effects of Contracting Out on Voluntary Turnover (Journal of Public and Nonprofit Affairs, 2021)
While public sector organizations have increasingly utilized New Public Management (NPM) strategies as a means of increasing the values of the market, a growing body of literature suggests that market-based reforms may generate indirect costs associated with negative organizational behaviors in the public sector. Focusing on probable consequences of government contracting out for the public workforce, this study examines the relationship between contracting out and voluntary turnover relying on a panel data of U.S. federal agencies from 2010 to 2017. The results present that contracting activity is associated with voluntary quits in the opposite direction depending on the level of job satisfaction. This finding disentangles the previous discussion on the relationship between NPM strategies and employee behavior.